Teacher Training & Assistance in Creating Creative Learning Media Using the Canva Application : Pelatihan & Pendampingan Guru dalam Pembuatan Media Pembelajaran Kreatif Menggunakan Aplikasi Canva - Iwan Abdy; Dwi Widyastuti Nurharyanto; Hutri Handayani Isra; Irham Wibowo; Roni Kurniawan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Era 5.0 has greatly influenced all aspects of life, including education. Era 5.0 is an era where all activities have experienced digitalization. In the education sector, digitalization is carried out on learning devices. One way to do this is by using the Canva application. The Canva application has several advantages: it is easy to access via various gadgets, and teachers have been given special access to get a premium account. Based on this, the Khairun University FKIP service team held a service at SDN 48 Ternate City. The service activity is